Barriers to People with HIV in Accessing Work: Systematic Review - Rio Ady Erwansyah; Amita Audilla; Ossi Dwi Prasetio; Nursalam Nursalam (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Problems that are often experienced by PLHIV are health, social, and economic problems. In addition, in everyday life, PLHIV experience problems in caring for themselves, meeting their social, economic, and psychological needs. PLHIV in accessing work are often hampered because of the stigma and discrimination they get and because of health factors that are easily exhausted. This research aims to find out the obstacles of PLHIV in accessing work. Systematic reviews were identified in four electronic databases published from 2016 to 2021. The quality of the reviewed studies was checked using the Critical Assessment Skills Program. The data were extracted by researchers and analyzed using thematic analysis. This review includes twelve eligible studies. The review found that stigma, support, environment and empowerment were the solutions and obstacles for PLHIV in accessing work. By providing support, there is no stigma, a good environment and empowering PLHIV can improve the quality of life and meet the primary needs of PLHIV. Barriers to accessing work experienced by PLHIV can be controlled through environmental empowerment by forming a support group.